Constant Winding Angle Curve on Revolution Surface and its Application. (March 2022) - Li, Haisheng; Li, Mingkun
Abstract: The fiber path plays an important role in determining the performance of composite wound parts. However, except for geodesics and semi-geodesics, available curves are few in filament winding, which limits the design space of composite wound parts. We present constant winding angle curve on revolution surface, and an upper limit estimation of its slippage coefficient. Furthermore, we introduce a sufficient and necessary condition to make it on cone nonslip, and show that it is a special semi-geodesic. For constant winding angle curve on revolution ellipsoid, we propose a sufficient condition that makes its slippage coefficient monotonically increasing, based on which an algorithm for determining nonslip constant winding angle curve is given. Constant winding angle curve provides a new way for the fiber path design of filament winding on revolution surface, which is demonstrated by its application in winding pressure vessels. By combining with semi-geodesics, we can optimize winding pattern for filament winding pressure vessels, which may wind the cylinder–dome transition region with constant winding angle curve, so that the fibers fully cover the mandrel as few overlap as possible. Highlights: Present constant winding angle curve on revolution surface, and give a sufficient condition to make it nonslip. Introduce a sufficient and necessary condition to make constant winding angle curve on cone nonslip. Propose a better sufficient condition for determining monotonicity of the slippage coefficient of constant winding angle curve on revolution ellipsoid, and an algorithm to determine its nonslip range. Develop a CAD system for filament winding pressure vessels using constant winding angle curve and semi-geodesics.